Nocebo Effects on Cowhage-evoked Itch: A Randomized Controlled Trial of Classical Conditioning and Observational Learning - Joseph S. Blythe; Kaya J. Peerdeman; Dieuwke S. Veldhuijzen; Myrthe M.E. van Schothorst; Mia A. Thomaïdou; Antoinette I.M. van Laarhoven; Andrea W.M. Evers (Medical Journals Sweden, 2021)
To investigate learning processes underlying nocebo effects on itch, this study measured the efficacy of classical conditioning and observational learning for inducing nocebo effects on cowhage-evoked itch and scratching behaviour. A total of 58 healthy female participants were assigned to classical conditioning, observational learning, or sham conditioning groups. In the classical conditioning group, experimenters associated the application of an inert gel with increased itch intensity themselves. In the observational learning group, a video of the conditioning paradigm was shown. Nocebo effects were measured as the difference in itch or scratching between control and nocebo test phase trials, compared between learning and control groups. Compared with sham conditioning, classical conditioning induced a significant nocebo effect on itch, while observational learning did not. No nocebo effect on scratching was detected. These results highlight the role that learning through direct experiences plays in pruritic symptoms. Future research should investigate how a patient's history of unsuccessful treatments shapes treatment outcomes.